Perceptions of Factors Influencing Diet and Eating Behaviors Among Latinx Middle School Students (P04-113-19) - Masek, Emily (Curr Dev Nutr, 2019)
OBJECTIVES: To better understand how Latinx middle school youth perceive the family- and environment-related factors that influence their diet and eating behaviors. METHODS: Five gender-stratified focus groups (3 with females, 2 with males) with 37 Latinx seventh grade students (54% female) were conducted. The guided discussion included questions about participants’ food choices, the role of their parents in their diet, the way diet and food are discussed at home, and healthy body-related concerns among their peers. Focus groups were audio recorded, transcribed verbatim, and coded in NVivo on the basis of specificity, extensiveness, frequency, and emotionality. Themes emerged from group dialogue; detailed conversations and predominant topics of discussion were noted. RESULTS: Youth identified several home- and family-level factors influencing their eating behaviors and food preferences, including parental/caregiver modeling, home food availability, and household budgetary constraints. Within the home, youth described a limited ability to participate in decisions regarding food choices, meal planning, meal preparation, and communicating with their caregivers about food preferences. Some youth expressed frustration due to perceiving that other family members were given alternative food options during meals. Youth were interested in eating healthier foods, but those options were not always available at home. Healthy foods at school were described as poorly prepared, and not always available. Youth reported experiencing peer pressure regarding healthy or unhealthy food selection, body image, and fitness level, and reported awareness of the use of unhealthful eating behaviors (e.g., restrictive eating, dieting, purging) as coping strategies. CONCLUSIONS: Family- and household-related factors emerged as important factors that influence youth dietary behaviors. Youth expressed they would eat more nutritious foods if they had more options, if the food was well prepared, and they were given more autonomy over their food and meal choices. Future diet interventions should incorporate strategies to address family-level and environmental factors that influence dietary intake in this vulnerable population. FUNDING SOURCES: Funded by NIMHD.